Russian book business in Estonia in the XIX - early XX centuries (based on materials of publishing activity in Narva) - S. V. Stepanov (Библиосфера, 2015)
The article is devoted to the history of Russian book business in Estonia. It traces publishing activities development in Narva - a city at the crossroads of cultures, gives a thematic-typological analysis of the publishing repertoire. The contribution characteristic of different ethnic groups in spreading Russian books at the Baltic States is represented based on studying typographers' social composition.